From co‐design to co‐production: Approaches, enablers, and constraints in developing a public health, capacity‐building solution. (17th October 2022) - Cosgrave, Catherine; Kennedy, Alison; Dietrich, Timo; Gunn, Kate; MacDonald, Joanna; McKay, Claire; Cunningham, Sally; Haren, Sam; Lewis, Josh
Abstract: Introduction: Investigating how co‐designed knowledge can be translated to co‐produce a public health capacity‐building solution for difficult‐to‐engage population groups drawing on the co‐production experience of a prevention‐focused, capacity‐building mental health solution targeting primary producers. Design: A qualitative study undertaken in rural and regional Victoria involving members of the design working group including project team (7px), digital design team (5px), marketing team (3px), and funding partner representatives. The study design involved reflective practice to collect data to identify the phases of co‐production and assess the design working group members' experiences. The analysis involved inductive coding using Braun and Clarke's thematic analysis. Objective: Identifying major points of divergence and/or convergence; enablers and/or constraints; and ways to better navigate and strengthen the co‐production process. Finding: Given members of the design working group, diverse skills sets divergence was experienced in all co‐production phases. Divergence was also experienced between the project team and the funding partner given the uniqueness of working conditions and requirements of workers in the primary production industry. The project team applied an iterative development process to project management; encouraging iterative cycles to create/test/revise among the teams, and with the funding partner, until each was satisfied with the end result (convergence). Discussion & Conclusion: When developing a co‐created public health prevention campaign it is critical that the project team focuses on relationship building among the members of the design working group and ensures adequate resourcing, development of shared understanding of project goals and target audience, ongoing communication, and a commitment to working iteratively.